The pilgrim's way to St. Patrick's Purgatory - Gardiner, Eileen (Italica Press, 2010)
"Based on an actual medieval pilgrimage route, this work traces a contemporary route from Dublin to Lough Derg, Donegal. It provides a cultural itinerary through Ireland's medieval past with its surviving, but fragmentary, riches, as it crosses the Irish borders and landscape, its rivers and lakes"--Provided by publisher